Campylobacter Polysaccharide Capsules: Virulence and Vaccines - Guerry, Patricia; Poly, Frederic; Riddle, Mark; Maue, Alexander C.; Chen, Yu-Han; Monteiro, Mario A. (Frontiers in Cellular and Infection Microbiology, 2012)
Campylobacter jejuni remains a major cause of bacterial diarrhea worldwide and is associated with numerous sequelae, including Guillain Barre Syndrome, inflammatory bowel disease, reactive arthritis, and irritable bowel syndrome. C. jejuni is unusual for an intestinal pathogen in its ability to coat its surface with a polysaccharide capsule (CPS). These capsular polysaccharides vary in sugar composition and linkage, especially those involving heptoses of unusual configuration and O-methyl phosphoramidate linkages. This structural diversity is consistent with CPS being the major serodeterminant of the Penner scheme, of which there are 47 C. jejuni serotypes. Both CPS expression and expression of modifications are subject to phase variation by slip strand mismatch repair. Although capsules are virulence factors for other pathogens, the role of CPS in C. jejuni disease has not been well defined beyond descriptive studies demonstrating a role in serum resistance and for diarrhea in a ferret model of disease. However, perhaps the most compelling evidence for a role in pathogenesis are data that CPS conjugate vaccines protect against diarrheal disease in non-human primates. A CPS conjugate vaccine approach against this pathogen is intriguing, but several questions need to be addressed, including the valency of CPS types required for an effective vaccine. There have been numerous studies of prevalence of CPS serotypes in the developed world, but few studies from developing countries where the disease incidence is higher. The complexity and cost of Penner serotyping has limited its usefulness, and a recently developed multiplex PCR method for determination of capsule type offers the potential of a more rapid and affordable method. Comparative studies have shown a strong correlation of the two methods and studies are beginning to ascertain CPS-type distribution worldwide, as well as examination of correlation of severity of illness with specific CPS types.